Patient change attributions in self-management of severe chronic fatigue syndrome. Issue 1 (2nd January 2017) - Adamowicz, J. L.; Caikauskaite, I.; Friedberg, F.; Seva, V.
ABSTRACT: Purpose: To identify patient change attributions arising from a home self-management intervention in severe chronic fatigue syndrome (CFS). Methods: This multi-method study of 126 participants with severe CFS collected data through phone interviews at 3-month follow-up in a self-management trial reported previously. Patient ratings (ranging from very much worse to very much better), were elicited on the global impression of change scale followed by this question: 'Why do you think you are: "worse", "unchanged", "improved"', etc.? The open-ended responses from participants were thematically organized and analyzed as study data. Results: Most improved participants referenced behavioral changes that included: increased relaxation, coping and stress reduction (44%), pacing (e.g. more rest, less exercise; 33%), and more physical activity/exercise (25%). For participants reporting 'unchanged' global ratings, the majority (63%) attributed their status to one or more of the following: nothing will help/illness acceptance/illness fluctuates without overall change (29%), everything is the same (24%) or does not know (17%). Participants with worsened global ratings most often attributed their decline to: changes in sleep (40.5%), deteriorating health (35%), specific life events (30%), and/or stress (30%). Treatment-assigned participants as compared to no treatment controls were significantly more likely ( p = <.05) to cite increased awareness, relaxation/coping/stress reduction and pacing as their reasons for change. The frequency of active vs. passive coping categories also distinguished improved from non-improved patients. Conclusions: Patient attributions could be utilized by the clinician to shift patient perceptions of their illness status in a constructive direction, possibly leading to an enhanced quality of life.